2017
DOI: 10.3390/data2020017
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Dataset of Soybean (Glycine max) Grown under Phosphorus-Deficient and -Sufficient Conditions

Abstract: This data descriptor introduces the dataset of the transcriptome of low-phosphorus tolerant soybean (Glycine max) variety NN94-156 under phosphorus-deficient and -sufficient conditions. This data is comprised of the transcriptome datasets (four libraries) acquired from roots and leaves of the soybean plants challenged with low-phosphorus, which allows further analysis whether systemic tolerance response to low phosphorus stress occurred. We describe the detailed procedure of how plants were prepared and treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Our previous RNA-Seq studies have shown that many genes involved in photosynthesis showed a significant change in the expression during low-P treatment in B20 [ 22 ]. These differentially-expressed genes (DEGs) were found to be mainly involved in photosynthesis, Calvin cycle, light reaction, carbon metabolism, photoreceptor, and photoprotection.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous RNA-Seq studies have shown that many genes involved in photosynthesis showed a significant change in the expression during low-P treatment in B20 [ 22 ]. These differentially-expressed genes (DEGs) were found to be mainly involved in photosynthesis, Calvin cycle, light reaction, carbon metabolism, photoreceptor, and photoprotection.…”
Section: Resultsmentioning
confidence: 99%
“…NGS technologies have now been applied to many important crop plants to help understand the genetics of complex traits, and to provide insight into genomic variations, such as single nucleotide polymorphisms (SNPs), insertions/deletions, and other structural of variances (O'Rourke, Bolon, Bucciarelli, & Vance, ; Valliyodan et al, ; Yuan, Bayer, Batley, & Edwards, ). These advanced technologies have also facilitated the development of gene expression atlases and increased our understanding of the signalling pathways involved in the responses of plants to environmental stresses (Abdelrahman et al, ; Abdelrahman, Suzumura, et al, ; Abdelrahman, El‐Sayed, Sato, et al, ; Bhattacharjee, Ghangal, Garg, & Jain, ; Nasr Esfahani et al, ; Zhang, Chu, & Zhang, ). However, during domestication, the genomes of many crop species have changed relative to that of their wild progenitors, with increasing numbers of repetitive DNA sequences that can lead to incomplete or misassembled regions when NGS is used for sequencing, as NGS‐read lengths are too short to adequately cover these repeats (Abdelrahman, Suzumura, et al, ; Flint‐Garcia, ; Pavlovich, ; Yuan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a shift in cultivated land use toward legume production can potentially lower the carbon footprint for the production of proteins needed for human consumption, increase N use efficiency, and enhance soil fertility (Considine et al, ; Foyer et al, ; Song et al, ; Sosa‐Valencia et al, ). However, the sustainability of legume crop production is threatened by the increasing incidence of environmental stresses, including persistent drought, increasing soil salinity, heat waves, and soil nutritional deficiencies (Aranjuelo, Cabrerizo, Aparicio‐Tejo, & Arrese‐Igor, ; Kunert et al, ; Maqbool, Aslam, & Ali, ; Nasr Esfahani et al, ; Valdés‐López et al, ; Zhang et al, ). For these reasons, it is essential to intensify legume genetic enrichment programmes, by using advanced breeding approaches and techniques, to develop legume cultivars that possess genetic resilience to environmental stresses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations